PERTANGGUNG JAWABAN PIDANA ANAK SEBAGAI KURIR NARKOTIKA - Muhammad Afrizal Pramudito; Rugun Romaida Hutabarat (LPPM Universitas Ekasakti Padang, 2023)
The role of children in narcotics crimes, namely as couriers for narcotics transactions, triggers a social phenomenon that strengthens because children are one of the next generations of the nation and are the foundation of their families and even themselves. Considering that there is a high rate of Narcotics crimes, especially the use of children as Narcotics couriers, this research aims to analyze the legal arrangements for children who become couriers in Narcotics crimes and criminal responsibility for children who become Narcotics police. This research is a normative legal research that relies on library research and uses other secondary legal materials. The data analysis used in this research is descriptive data analysis method. The results of this study indicate that for children who become Narcotics couriers in Narcotics crimes, these children can be referred to as falling into major criminal acts. Criminal responsibility for children who become Narcotics couriers and are caught in Narcotics criminal cases will first be assessed for the age of the child to determine the punishment he will receive because when the child is 12-13 years old, he will only be subject to sanctions while if he is 14-16 years old years shall be sentenced to half the maximum threat of adult punishment